The Effect of Inflation and Corporate Social Responsibility (CSR) on Return Stocks with Profitability as an Intervening Variable in the Sector Mining Listed on the Indonesia Stock Exchange - Sri Puspa Nurhayati; Yusuf Imam Suja’i; Agus Salim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The mining sector (Mining index) is an index composed of various shares of mining sector issuers listed on the Indonesia Stock Exchange. Indonesia's dependence on the mining sector as a supporter of the economy is reflected in the large contribution of the mining sector to state revenues. Factors that affect stock returns are macroeconomic factors and fundamental factors. Macroeconomic factors stem from broad economic problems, one of which is inflation. This fundamental factor can be seen from the financial statements, and the issuer's financial statements can be seen from the level of financial performance both in terms of the ability to generate profits (profitability). This study aims to prove the effect of inflation and corporate social responsibility on stock returns with profitability as an intervening variable in the mining sector listed on the Indonesia Stock Exchange. The population of this study is 47 mining sector companies listed on the Indonesia Stock Exchange. The sampling technique uses a purposive sampling method that has certain criteria in taking samples that have the 2019-2021 annual financial statements, in order to obtain 141 company. This research method uses Structural Equation Modeling (SEM) analysis based on variance, namely Partial Least Square (PLS). SEM with PLS is based on variance so that it can handle two conditions, namely conditions with undetermined factors and conditions where the solution cannot be accepted. The analysis used includes descriptive analysis, convergent validity, discriminant validity, construct reliability, R-square, and hypothesis testing. Based on the results of research that has been done, the variables that have a significant effect on stock returns are profitability variable and corporate social responsibility (CSR) variable.